Effect of sorghum and methionine supplementation in productive performance and the quality of hatching eggs of two quail strains - Younis, D. Th. (The Iraqi Journal of Veterinary Medicine, 2014)
The aim of the present study was to identify the effect of corn replacement by sorghum and supplementation of methionine during growing and laying periods in productive performance and egg quality of two strains of quail (brown and black). Four hundred and eighty quails (240 of each strain) were used in this study. Birds reared on floor letter in semi opened house distributed into four treatments each with three replicates (20 birds in replicate). Experimental treatments were as follows: T1: fed on yellow corn ration (Control), T2: fed on ration in which 50% of corn replaced by sorghum , T3: fed on ration in which 50% of corn replaced by sorghum and supplemented with 0.2% methionine and T4: fed on ration in which 50% of corn replaced by sorghum and supplemented with 0.4% methionine . Statistical analysis of data showed no significant differences (P≤0.05) between treatments and strains in live body weight, average weekly weight gain, feed consumption, feed conversion ratio dressing percentage and mortality rate. After sexual maturity age no differences were observed between the treatments and strains in egg production HD%, egg weight, feed conversion ratio, egg shape index, shell weight, shell thickness, albumin height, yolk dimension, yolk height, blood glucose, blood triglyceride, blood total protein, blood hemoglobin, ALT and AST enzymes concentration in serum through out of the experimental period which was lasted for 99 days. In conclusion, the results revealed the possibility of 50% sorghum replacement instead of yellow corn without any passive effects on productive performance which reduce the productive costs.